2006
DOI: 10.1007/s11483-006-9016-1
|View full text |Cite
|
Sign up to set email alerts
|

Small and Large Deformation Rheology of Acid Gels from Transglutaminase Treated Milks

Abstract: The purpose of this study was to evaluate the effects of microbial transglutaminase on the rheological and mechanical properties of gels from a commercial UHT milk made by acidification with D-gluconic-acid-δ-lactone. Although further heating of UHT milk, primarily carried out to inactivate the enzyme, showed a significant impact on gel firmness, we observed no enzyme-related effects at small deformation. The impact of the additional thermal treatment was also evident in large deformation measurements. In thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…3A). Similar results were reported by Schorsch, Carrie, and Norton (2000), while others (Anema, Lauber, Lee, Henle, & Klostermeyer, 2005;Jaros, Patzold, Schwarzenbolz, & Rohm, 2006b;Lauber, Henle, & Klostermeyer, 2000;Lorenzen, Mautner, & Schlimme, 1999) have observed that pre-treatment of milk with TGase yields firmer acid milk gels. The mechanism for the TGaseinduced increase in acid-flocculation pH has not been elucidated thus far.…”
Section: Colloidal Stability Of Casein Nanogel Particlessupporting
confidence: 88%
“…3A). Similar results were reported by Schorsch, Carrie, and Norton (2000), while others (Anema, Lauber, Lee, Henle, & Klostermeyer, 2005;Jaros, Patzold, Schwarzenbolz, & Rohm, 2006b;Lauber, Henle, & Klostermeyer, 2000;Lorenzen, Mautner, & Schlimme, 1999) have observed that pre-treatment of milk with TGase yields firmer acid milk gels. The mechanism for the TGaseinduced increase in acid-flocculation pH has not been elucidated thus far.…”
Section: Colloidal Stability Of Casein Nanogel Particlessupporting
confidence: 88%
“…Measurements were started within 1 min after addition of GDL. During gelation a strain of 0.003, low enough to ensure undisturbed gelation (Jaros et al, 2006b), was applied at a frequency of 1 rad s À1 . Storage modulus, G 0 (Pa) and loss tangent, tan d (À), were monitored as a function of time.…”
Section: Dynamic Low-deformation Rheologymentioning
confidence: 99%
“…In several studies on whole or skim milk, the action of mTGase has been controlled by inactivation through heating (e.g., Anema, Lauber, Lee, Henle, & Klostermeyer, 2005;Jaros, Pä tzold, Schwarzenbolz, & Rohm, 2006b;Lauber et al, 2000;Sharma, Lorenzen, & Qvist, 2001). As the heat-induced denaturation of whey proteins also contributes to the rheological properties of acid milk gels, a careful design of the experiments is necessary to allow a causal assignment of the observed effects (Jaros et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the protein matrix, which is mainly formed of weak physical interactions, directly by introducing strong covalent bonds within or between protein particles is one method to improve structural properties of skim milk gels. Use of transglutaminase (TG), a transferase which creates (g-glutamyl)-lysine isopeptide linkages (Folk & Finlayson, 1977;Griffin, Casadio, & Bergamini, 2002), for that purpose has been extensively studied and reviewed Jaros, Partschefeld, Henle, & Rohm, 2006;Ozrenk, 2006). We have previously shown the effects of TG on texture and microstructure of acid-induced skim milk gels with the emphasis on the effect of pre-heat treatment (Ercili Cura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%